IMPLEMENTASI PROGRAM PENDIDIKAN KARAKTER DI SEKOLAH DASAR NEGERI LAWANGGINTUNG 01 KOTA BOGOR - Pertiwi, Ravhi; Suchyadi, Yudhie; ., Sumardi; ., Rukmini (Program Pendidikan Guru Sekolah Dasar Universitas Pakuan, 2019)
This research is use qualitative descriptive approach. The purpose of this research is to describe how the planning and the implementation of charactereducation in SDN Lawanggintung 01. The result of this research is the planningof chacarcter education is start with analyst how the condition and potency in this school to decide the value of character which will be implemented there are religious, nationalis, indeoendent, discipline, like to read, appreciate achievement, environmental care.Integrating the main character and values matched with the standards of com-petence and basic competence, suitability with the material. The implementation of character education was realized through teach character values in layers of artefacts on school culture with provide the infrastructure that will support the character education program. The program of character education was designed to build student character through the habituation at school who can make student familiarize by theirselves about character values which has been planned in school. From the result of the research above can be concluded that the implementation of character education in SDN Lawanggintung 01 has been implemented well from the planning to the implementation.